The unwinding of apartheid : UK-South African relations, 1986-1990 - Salmon, Patrick; Jewitt, Martin (London : Routledge, Taylor & Francis Group, 2019)
This volume examines diplomatic relations between the United Kingdom and South Africa from 1986 to 1990, when deadlock gave way to the first stages in the unwinding of apartheid. By the middle of 1986, the South African Government had succeeded in containing the township revolt, but its hesitant moves towards reform had brought the end of apartheid no closer. The intransigent figure of President P.W. Botha ensured a continuing stalemate until his reluctant departure from office in August 1989. The subsequent election of F.W. de Klerk marked the beginning of irrevocable change, symbolised by the release of Nelson Mandela from prison in February 1990. This volume documents the role of the United Kingdom in keeping pressure on the South African Government, building contacts with the African National Congress (ANC) and giving decisive encouragement to President de Klerk's reform initiatives. It reveals recurrent differences of approach between the Foreign and Commonwealth Office and Prime Minister Margaret Thatcher. However, it also shows that despite her frequent confrontations with the international community in general, and the Commonwealth in particular, Mrs Thatcher repeatedly brought pressure to President Botha and strongly supported President de Klerk during his first crucial months in office. Her part in bringing about change in South Africa was fully appreciated by Nelson Mandela, whose first meeting with Mrs Thatcher concludes the volume. This book will be of much interest to students of British politics, African studies, foreign policy and International Relations in general
Includes bibliographical references and index.